Screening of biosynthesized zinc oxide nanoparticles for their effect on Daucus carota pathogen and molecular docking. Issue 10 (1st July 2022) - Khan, Azhar U.; Khan, Masudulla; Malik, Nazia; Parveen, Aiman; Sharma, Poonam; Min, Kim; Gupta, Mona; Alam, Mahboob
Abstract: Herein, we investigate the phytogenic synthesis of zinc oxide nanoparticles (ZnO‐NPs) by using aqueous extract of seed coat of almond as a novel resource which can acts as a stabilizing and reducing agents. Successful biosynthesis of ZnO‐NPs was observed by Ultraviolet–visible spectroscopy (UV–vis) showing peak at 272 nm. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques confirm the circular shape with an average size of 20 nm. Applications of ZnO‐NPs were observed on carrot ( Daucus carota ) plant infected with pathogenic fungus Rhizoctonia solani . Spray with 50 ppm and 100 ppm ZnO‐NPs caused significant increase in plant growth attributes and photosynthetic pigments of carrot plants. It has been reported that the synthesized ZnO‐NPs demonstrated an inhibitory activity against plant pathogenic fungus R. solani and reduces disease in carrot plants . Scanning electron microscopy and confocal microscopy indicated adverse effect of ZnO‐NPs on pathogens. Antifungal efficiency of ZnO‐NPs was further explained with help of molecular docking analysis. Conformation with highest negative binding energy was used to predict binding site of receptor with NPs to know mechanistic approach. ZnO‐NPs are likely to interact with the pathogens by mechanical enfolding which may be one of the major toxicity actions against R. solani by ZnO‐NPs. Research highlights: ZnO nanoparticles were synthesized using waste material from the coat of almond seeds. Images from SEM, TEM, and related techniques like EDS and SAED revealed the irregularity of the ZnO NPs as well as their atom composition. FTIR and XRD analyses confirmed the formation and the presence of crystalline ZnO NPs in nature. Biogenic ZnONPs were found to be effective against the plant pathogenic fungus R. solani . A spray of 50 ppm and 100 ppm ZnO‐NPs significantly increased carrot plant growth characteristics and photosynthetic pigments. Abstract :